(untitled) (Kriminalističke teme, 2020)
Reason for writing and research problem(s): Life-course criminology - within which developmental criminology is incorporated - is an approach to examining criminal behavior over time. More specifically age-graded sequences, including broader social, psychological, and other contexts that are meaningful and prone to change. Research on criminal careers is based on changes in crime patterns, which occur during development, i.e. within the life course of an individual. Criminal careers are most researched area within criminology. Although much knowledge about criminal careers has accumulated over the past few decades, research on perpetrators of organized crime has been extremely reduced. Aims of the paper (scientific and/or social): The aim of this paper is to present the state-of-the-art of the research of criminal careers in organized crime. Methodology/Design: The paper presents a traditional literature review. Therefore, the narrative discussion of previous research was used. Research/Paper limitation: This is paper does not discuss the verification of previous research in the context of Bosnia and Herzegovina. Due to the limited scope of the paper detailed information on life course/developmental criminology has been reduced. Results/Findings: Studies have demonstrated that perpetrators most often start their criminal careers late - in adulthood - and that they are not specialists in organized crime. The findings so far have been limited by different research approaches. Most studies have applied quantitative techniques. General Conclusion: Studies demonstrated that life-course/developmental criminology must have a greater focus on adults. The situational factors that lead to crime have been neglected, which has direct implications for limited knowledge of criminal careers in organized crime. More research is needed, especially in the Balkans. Research/Paper Validity: Life-course/developmental criminology has been neglected in Bosnia and Herzegovina and the region. This paper seeks to contribute to and expand the existing knowledge fund.